The Right of Ownership Accruing to the Religious According to the Code of Canon Law. An Outline (Global Journal of Human-Social Science, 2023)
The religious state is essentially neither laity nor clergy It is deemed the third state specifically bound by the evangelical counsels of obedience chastity and poverty1 From the analysed point of view the evangelical counsel of poverty and partly obedience has special importance The essence of the evangelical counsel of poverty is how the individual practising it sees temporal possessions There is no doubt that this primarily concerns the spiritual aspect but the evangelical counsel of poverty also has a legal dimension The evangelical counsel of poverty refers to all legal relationships concerning temporal possessions However its most significant and spectacular concern is the right of ownership accruing to the religious Indeed ownership is by its very nature the most extensive right to a particular item goods hence constituting the most essential part of the evangelical counsel of poverty This paper analyses how and why the evangelical counsel of poverty taking the form of the vow of poverty affects and determines the right to ownership accruing to the religious It investigates whether and how the right to ownership accruing to the religious is limited and divested